PWE-095 Faecal Calprotectin Is Useful In Predicting Long Term Disease Recurrence In Post-operative Crohn's. (9th June 2014) - Perowne, R; Lamb, C; Speight, RA; Price, M; Mansfield, J
Abstract : Introduction: The concept of using faecal biomarkers to predict prognosis and direct treatment in patients with Crohn's disease is attractive but long term follow-up data is lacking. A cohort of 51 patients with previous ileal resections for Crohn's disease provided a one-off stool sample for faecal calprotectin (FC). These patients were followed up for 5 years to assess whether FC could predict disease progression in the long term. Methods: Patients were identified from a database of patients who had participated in a previous study evaluating the use of FC in post-operative Crohn's. Patients were included in the study if they had been followed up for at least 5 years after the initial FC was recorded. Case notes were reviewed retrospectively and information on the need for escalation of medical therapy or for further surgery for disease recurrence was recorded. A FC of more than 200 was taken as the cut-off value for evidence of active inflammation. Statistical analysis was performed using Prism 6 (GraphPad Software, San Diego, USA). Results: 17 patients had a FC ≥ 200 (median 751, IQR 593–916). Of these 13 required either escalation of medical treatment and/or further surgery over the 5 year follow-up period. 34 patients had a FC <200 (median 18, IQR 4–71). Of these 11 required treatment escalation and/or surgery. A FC of ≥200 correlated significantly with need for escalation of medical treatment and/or further surgery over a 5 year follow up (p 0.003). Conclusion: A FC of less than 200 predicts a better prognosis in patients with post-op Crohn's disease over a prolonged (5 year) period and could therefore potentially be used to stratify treatment and target early intervention. Disclosure of Interest: None Declared.